Monitoring Cutaneous Leishmaniasis Lesions in Mice Undergoing Topical Miltefosine Treatment - Laura Fernanda Neira; Julio Cesar Mantilla; Patricia Escobar (MDPI AG, 2023)
A study was conducted on BALB/c mice infected with Leishmania (Leishmania) amazonensis to analyse the effects of 0.5% miltefosine (MTF) hydrogel treatment on cutaneous leishmaniasis (CL) lesions. The mice were treated for 25 days topically, and lesion sizes, parasite loads, histopathology, ultrastructure, cytokines including interleukin 4 (IL-4), tumour necrosis factor alfa (TNFα), interferon gamma (IFNγ), IL-10, and vascular endothelial growth factor (VEGF) profiles were evaluated on days 0, 12, 25, and 85. After 12 days of treatment, the lesion sizes and parasite numbers decreased. By day 60 post treatment, there were no lesions and only a few parasites. At day 25, there was a temporary papillomatosis reaction, an increase in mast cells, a few giant cells, and granulomas, and a decrease in diffuse inflammatory infiltrate and parasites. Transmission electron microscopy (TEM) examination showed early ultrastructural changes, including macrophages without parasites and vacuoles containing electrodense material. At the different evaluated times, the cytokine regulation indexes (ICRs) decreased for IL-4, TNFα, and VEGF. According to the study, the 0.5% MTF hydrogel was effective and showed positive results from the early stages of usage. The MTF directly targeted parasites, downregulated the release of IL-4, TNFα, and VEGF, increased mast cell production, and induced granuloma reaction during evaluation periods.